Assessment of physicochemical and thermal properties of soluble dextrin fiber from potato starch for use in fruit mousses. (7th January 2021) - Kapusniak (Jochym), Kamila; Wojcik, Malwina; Wrobel, Karolina; Rosicka‐Kaczmarek, Justyna; Kapusniak, Janusz
Abstract: BACKGROUND: Fruit mousses are products with a relatively low amount of dietary fiber in a single portion, but with additional portions of soluble fiber they may be good alternative to fiber‐rich snacks as take‐away food. In the present study, the properties of new soluble dextrin fiber (SDexF) from potato starch were assessed to establish whether it could be used to enrich fruit mousses. The properties of SDexF that can affect processing and storage stability of enriched mousses were studied and compared with those of native potato starch and semiproducts (resulting from various drying temperatures). The effect of the addition of SDexF on the pasting properties of mousse was also analyzed. RESULTS: The application of food‐grade hydrochloric and citric acids as catalysts in the dextrinization of food‐grade potato starch allowed to SDexF to be obtained. Despite the differences in characteristics of the semiproducts, the final SDexF preparations were very similar in the meaning of solubility, dextrose equivalent (DE), retrogradation, and pasting properties. SDexF preparations were characterized by a significantly lower retrogradation tendency, peak viscosity, final viscosity, and gelatinization enthalpy in comparison with both native starch and semiproducts. Soluble dextrin fiber was successfully added to banana‐apple mousse. The addition of SDexF to mousse did not cause any undesirable changes to the viscosity of the product, and surprisingly even resulted in mousse with lower viscosity. Turbidity and RVA studies revealed that SDexF was stable and retrogradation processes can be negligible during storage. CONCLUSION: The SDexF obtained from potato starch can be a novel functional substance to increase the dietary fiber content of fruit or fruit and vegetable mousses. © 2020 Society of Chemical Industry